LARGE-SCALE EROSION RATES FROM IN SITU-PRODUCED COSMOGENIC NUCLIDES IN EUROPEAN RIVER SEDIMENTS - Schaller M.; von Blanckenburg F.; Hovius N.; Kubik P.W. (My University, 2001)
We have calculated long-term erosion rates of 20-100 mm/kyr from quartz-contained 10Be in the bedload of middle European rivers for catchments ranging from 102 to 105 km2. These rates average over 10-40 kyr and agree broadly with rock uplift, incision and exhumation rates, historic soil erosion rates, and erosion rates calculated from the measured sediment loads of the same rivers. Moreover, our new erosion rate estimates correlate well with lithology and relief. However, in the Regen, Neckar, Loire, and Meuse catchments, cosmogenic nuclide-derived erosion rates are consistently 1.5-4 times greater than the equivalent rates derived from measured river loads. This may be due to the systematic under-representation of high-magnitude, low-frequency transport events in the gauging records which cover less than a century. Alternatively the discrepancy may derive from spatially non-uniform erosion and preferential tapping of deeper sections of the irradiation profile. A third explanation relates the high cosmogenic nuclide-derived erosion rates to inheritance of an elevated Pleistocene erosion signal. Uncertainties associated with the cosmogenic nuclide-derived erosion rate estimates are not greater than the potential errors in conventional estimates. Therefore, the cosmogenic nuclide approach is an effective tool for rapid, catchment-wide assessment of time-integrated rates of bedrock weathering and erosion, and we anticipate its fruitful application to the Quaternary sedimentary record.
Keywords: EROSION; BE-10; COSMOGENIC ELEMENTS; EUROPE; Quaternary; Pleistocene; Кайнозой::Четвертичная::Плейстоцен; Cenozoic::Quaternary; Cenozoic::Quaternary::Pleistocene; Кайнозой::Четвертичная